2011
DOI: 10.5539/ass.v7n7p64
|View full text |Cite
|
Sign up to set email alerts
|

School Facilities and Academic Achievement of Secondary School Agricultural Science in Ekiti State, Nigeria

Abstract: The study looked at the provision of facilities as it relates to academic performance of students in agricultural science in Ekiti state of Nigeria between 1990 and 1997. The study population was results of the West African School Certificate Examinations (WASCE) conducted between 1990 and 1997 in 50 secondary schools in both rural and urban areas of the state. One validated instrument (S TQF ) was used for data collection. One hypothesis was formulated and answered. Data were analysed using mean and t -test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
40
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 10 publications
(5 reference statements)
12
40
1
4
Order By: Relevance
“…Schools without basic facilities and resources such as prescribed textbooks often have low academic performance. [30] Owoeye and Yara [31] stipulate that the main purpose of a school library is to make all books, periodicals and other reproduced materials available to the students. They further indicated that school libraries may not be effective if the books therein are not adequate and up to date.…”
Section: Discussionmentioning
confidence: 99%
“…Schools without basic facilities and resources such as prescribed textbooks often have low academic performance. [30] Owoeye and Yara [31] stipulate that the main purpose of a school library is to make all books, periodicals and other reproduced materials available to the students. They further indicated that school libraries may not be effective if the books therein are not adequate and up to date.…”
Section: Discussionmentioning
confidence: 99%
“…Penilaian subjektif siswa tentang sekolah dalam hal ini yaitu tentang pelayanan dan fasilitas sekolah yang diharapkan mampu menunjang proses pembelajaran di lingkungan sekolah sangatlah penting, karena dengan adanya dukungan fasilitas sekolah diharapkan siswa memiliki rasa puas dalam lingkungan belajarnya (Owoeye & Yara, 2011). Penelitian yang dilakukan oleh Konu dan Lintonen (2005) mengungkapkan kondisi fisik sekolah yang paling perlu ditingkatkan aspek having yang mempengaruhi kepuasan siswa adalah ventilasi, fasilitas toilet, dan suhu, yang merupakan beberapa indikator dari aspek having yang mempengaruhi kepuasan siswa.…”
Section: Hasil Dan Pembahasan Gambaran School Well-being Siswa Kelas unclassified
“…Teachers demonstrate experiments instead and so the student-centered characteristic as claimed by the DepEd's K-12 is not happening in chemistry instruction. The study of Owoeye & Yara (2011) has proven that school facilities were the most potent determinant of academic achievement. Facilities in terms of qualifications of personnel, who are directly involved in the pedagogy; laboratory, library, school buildings, chairs/tables, administrative blocks, chalk-board, school maps, and the like are very crucial to high academic attainment.…”
Section: Don't' Want That Because I'm Lazy (R6)mentioning
confidence: 99%